The Relevance of Patents as Collateral for Loans in Supporting an Innovation-Based Economy in Indonesia - Kiki Juwita; Alieffa Nanda; Ria Wierma Putri; Sepriyadi Adhan S (Journal of Law, Politic and Humanities, 2026)
The transformation towards an innovation-based economy positions patents as a strategic instrument that not only serves as legal protection but also as a highly valuable economic asset. This study aims to analyze the legal strength of patents as credit collateral in banking practices in Indonesia and to examine their relevance and optimal use in supporting an innovation-based economy. The research method used is normative juridical with a statutory and conceptual approach, utilizing primary, secondary, and tertiary legal materials analyzed qualitatively. The results show that, normatively, patents meet the criteria for collateral, as they are classified as intangible movable objects with economic value and can be bound by fiduciary guarantees. However, in banking practice, their use remains limited due to valuation constraints, low liquidity, and the lack of a clear execution mechanism. On the other hand, the use of patents as credit collateral is highly relevant in increasing access to financing for innovative entrepreneurs, strengthening the creative economy ecosystem, and enhancing national competitiveness. Therefore, strengthening regulations, developing assessment systems, and synergy between institutions are needed to optimize the role of patents as a financing instrument in supporting innovation-based economic growth in Indonesia.